Targeted AAVP-based therapy in a mouse model of human glioblastoma: a comparison of cytotoxic versus suicide gene delivery strategies - Staquicini, Fernanda I. (Cancer Gene Ther, 2019)
Glioblastoma persists as a uniformly deadly diagnosis for patients and effective therapeutic options are gravely needed. Recently, targeted gene therapy approaches are reemerging as attractive experimental clinical agents. Our ligand-directed hybrid virus of adeno-associated virus and phage (AAVP) is a targeted gene delivery vector that has been used in several formulations displaying targeting ligand peptides to deliver clinically applicable transgenes. Here we compared different constructs side-by-side in a tumor model, an orthotopic model of xenograft human glioblastoma cells stereotactically implanted in immunodeficient mice. We have used divergent therapeutic strategies for two AAVP constructs, both displaying a double-cyclic RGD4C motif ligand specific for alpha V integrins expressed in tumor vascular endothelium, but carrying different genes of interest for the treatment of intracranial xenografted tumors. One construct delivered tumor necrosis factor (TNF), a purely cytotoxic gene for antitumor activity (RGD4C-AAVP-TNF); in the other construct, we delivered Herpes simplex virus thymidine kinase (HSVtk) for in tandem molecular-genetic imaging and targeted therapy (RGD4C-AAVP-HSVtk) utilizing ganciclovir (GCV) for a suicide gene therapy. Both AAVP constructs demonstrated antitumor activity, with damage to the tumor-associated neovasculature and induction of cell death evident after treatment. In addition, the ability to monitor transgene expression with a radiolabeled HSVtk substrate pre and post GCV treatment demonstrated the theranostic potential of RGD4C-AAVP-HSVtk. We conclude that targeted AAVP constructs delivering either cytotoxic TNF or theranostic HSVtk followed by suicide gene therapy with GCV have comparable preclinical efficacy, at least in this standard experimental model. The results presented here provide a blueprint for future studies of targeted gene delivery against human glioblastomas and other brain tumors.